STEM LEARNING: FERMENTATION EXPERIMENT AS A BRIDGE BETWEEN MICROBIAL BIOLOGY AND CHEMICAL REACTIONS - Rizki, Cut Novrita; Fajriana, Nurul; Aini, Qurratu (Jurnal Biologi Sains dan Kependidikan, 2025)
STEM (Science, Technology, Engineering, Mathematics)-based learning is designed to enhance 21st-century competencies in students through interdisciplinary integration and project-based activities. This study examines the implementation of fermentation experiments as a STEM learning medium in the Biology Education (Tadris Biologi) course at Universitas Muhammadiyah Aceh. Fermentation experiments (such as making tempeh or yogurt) involve microbial biology concepts (roles of yeast/bacteria) and chemical reactions (conversion of sugars into ethanol or acids), thus enabling the integration of science and mathematics in real-world contexts. The research employed a quasi-experimental design involving undergraduate students of Biology Education. Data were collected through pre- and post-learning concept tests, laboratory activity observations, and questionnaires measuring 21st-century skills (4Cs). The results showed a significant improvement in students’ conceptual understanding of fermentation and in their critical thinking, creativity, collaboration, and communication skills. Students actively posed critical questions regarding biochemical changes during fermentation and demonstrated enhanced teamwork and creativity in designing experiments. Overall, the fermentation experiments effectively bridged microbial biology and chemical reaction concepts while strengthening 21st-century skills, in line with previous research findings. This study implies that STEM integration through fermentation experiments can improve science literacy among Biology Education students and is recommended for higher education curricula.